2014
DOI: 10.1302/0301-620x.96b5.32362
|View full text |Cite
|
Sign up to set email alerts
|

A new morphological classification for greater tuberosity fractures of the proximal humerus

Abstract: In this study, we describe a morphological classification for greater tuberosity fractures of the proximal humerus. We divided these fractures into three types: avulsion, split and depression. We retrospectively reviewed all shoulder radiographs showing isolated greater tuberosity fractures in a Level I trauma centre between July 2007 and July 2012. We identified 199 cases where records and radiographs were reviewed and included 79 men and 120 women with a mean age of 58 years (23 to 96). The morphological cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 28 publications
6
74
3
3
Order By: Relevance
“…[22][23][24][25][26] This poor reliability persists even when GT fractures are evaluated in isolation (Neer interobserver/intraobserver 0.31 to 0.35/0.54 to 0.63 and AO interobserver/intraobserver 0.30 to 0.35/0.59 to 0.65). 26,27 The poor reliability of the AO and Neer classifications is likely the result of difficulty in measuring GT displacement using radiography. 18,19,28 However, many studies have shown persistently poor reliability despite the use of radiographic aids, such as stereovisualization and three-dimensional CT. 22,23,26 The Neer and AO classification systems are based solely on fragment displacement 20,21 and do not take into account GT fragment size, morphology, or orientation.…”
Section: Classificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26] This poor reliability persists even when GT fractures are evaluated in isolation (Neer interobserver/intraobserver 0.31 to 0.35/0.54 to 0.63 and AO interobserver/intraobserver 0.30 to 0.35/0.59 to 0.65). 26,27 The poor reliability of the AO and Neer classifications is likely the result of difficulty in measuring GT displacement using radiography. 18,19,28 However, many studies have shown persistently poor reliability despite the use of radiographic aids, such as stereovisualization and three-dimensional CT. 22,23,26 The Neer and AO classification systems are based solely on fragment displacement 20,21 and do not take into account GT fragment size, morphology, or orientation.…”
Section: Classificationsmentioning
confidence: 99%
“…In 2014, Mutch et al 27 proposed a morphologic classification using a series of 199 isolated GT fractures. The interobersever/intraobserver reliability was 0.73 to 0.77 and 0.69 to 0.86, respectively.…”
Section: Classificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on the split fracture type, which typically involves a large fragment with a fracture line from supero-medial to inferolateral angled 50°with respect to the humeral shaft. This type represents 41% of GT fractures (Mutch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The split type, which also makes up 41% of all cases, consists of a fracture line oriented approximately 50°to the humeral shaft. The depression fracture is the least common (18%) and represents an impaction of the GT(Mutch et al, 2014).…”
mentioning
confidence: 99%